2020
DOI: 10.1021/acs.energyfuels.0c00874
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Asphaltene Nanostructures and Thermodynamic Applications

Abstract: Previously, asphaltene science had been hindered by many significant uncertainties regarding molecular weight, molecular structure, and nanocolloidal characteristics in laboratory solvents and crude oils. These debates were of sufficient magnitude to forestall development and utility of asphaltene modeling for various applications. In the last 2 decades, advances in asphaltene science using many sophisticated techniques have greatly reduced corresponding uncertainties, enabling development of simple asphaltene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
163
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(167 citation statements)
references
References 163 publications
4
163
0
Order By: Relevance
“…This approximate size window is a result of the preparation method used. The molecules are sublimed by resistive flash heating from a piece of oxidized silicon wafer in ultra-high vacuum (UHV) (Schuler et al 2015(Schuler et al , 2020 onto the sample held at T = 10 K. Some of the small molecules (about two rings and less) are too volatile and thus might leave the wafer before the evaporation step. On the other side, large molecules (about 20 rings and more) tend to fragment before their sublimation.…”
Section: Resultsmentioning
confidence: 99%
“…This approximate size window is a result of the preparation method used. The molecules are sublimed by resistive flash heating from a piece of oxidized silicon wafer in ultra-high vacuum (UHV) (Schuler et al 2015(Schuler et al , 2020 onto the sample held at T = 10 K. Some of the small molecules (about two rings and less) are too volatile and thus might leave the wafer before the evaporation step. On the other side, large molecules (about 20 rings and more) tend to fragment before their sublimation.…”
Section: Resultsmentioning
confidence: 99%
“…At present, it is considered that the molecular structure unit models of asphaltenes are mainly "group island type", "continental type" and "mixed type" (Fernando et al 2013). Schuler et al (2015Schuler et al ( , 2017Schuler et al ( , 2020) demonstrated the first direct observation of wide diversity of asphaltene molecular motifs with peri-and cata-condensed polycyclic aromatic hydrocarbons (PAHs). Various types of coal-derived asphaltene structures were obtained by the atomic force microscopy.…”
Section: )mentioning
confidence: 99%
“…These breakthroughs have to a great extent provided answers as well as providing evidence to earlier debates on molecular weight and structural models of asphaltenes. [13][14][15][16] It's now generally accepted that "island" or "aryl linked core" models are more representative of asphaltenes whereas the archipelago model has been either redened or has been neglected entirely. 13 With this new information coming to light; in this paper we combine this microscopy information with results obtained using renown spectroscopic methods to characterize and assign chemical structures to these asphaltenes.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] It's now generally accepted that "island" or "aryl linked core" models are more representative of asphaltenes whereas the archipelago model has been either redened or has been neglected entirely. 13 With this new information coming to light; in this paper we combine this microscopy information with results obtained using renown spectroscopic methods to characterize and assign chemical structures to these asphaltenes. Various studies in the past have shown that these methods can be used to effectively characterize asphaltenes although did not answer the questions on the type of model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation